Formulation, Characterisation and Stabilisation of Buccal Films for Paediatric Drug Delivery of Omeprazole - Khan, Sajjad (AAPS PharmSciTech, 2015)
This study aimed to develop films for potential delivery of omeprazole (OME) via the buccal mucosa of paediatric patients. Films were prepared using hydroxypropylmethylcellulose (HPMC), methylcellulose (MC), sodium alginate (SA), carrageenan (CA) and metolose (MET) with polyethylene glycol (PEG 400) as plasticiser, OME (model drug) and L-arg (stabiliser). Gels (1% w/w) were prepared at 40°C using water and ethanol with PEG 400 (0–1% w/w) and dried in an oven (40°C). Optimised formulations containing OME and L-arg (1:1, 1:2 and 1:3) were prepared to investigate the stabilisation of the drug. Tensile properties (Texture analysis, TA), physical form (differential scanning calorimetry, DSC; X-ray diffraction, XRD; thermogravimetric analysis, TGA) and surface topography (scanning electron microscopy, SEM) were investigated. Based on the TA results, SA and MET films were chosen for OME loading and stabilisation studies as they showed a good balance between flexibility and toughness. Plasticised MET films were uniform and smooth whilst unplasticised films demonstrated rough lumpy surfaces. SA films prepared from aqueous gels showed some lumps on the surface, whereas SA films prepared from ethanolic gels were smooth and uniform. Drug-loaded gels showed that OME was unstable and therefore required addition of L-arg. The DSC and XRD suggested molecular dispersion of drug within the polymeric matrix. Plasticised (0.5% w/w PEG 400) MET films prepared from ethanolic (20% v/v) gels and containing OME: L-arg 1:2 showed the most ideal characteristics (transparency, ease of peeling and flexibility) and was selected for further investigation.